Gut microbiota, a hidden protagonist of traditional Chinese medicine for acute ischemic stroke - Gao, Lin; Xia, Xiuwen; Shuai, Yinqi; Zhang, Hong; Jin, Wei; Zhang, Xiaoyun; Zhang, Yi (Frontiers in Pharmacology, 2023)
Acute ischemic stroke (AIS) is one of the leading diseases causing death and disability worldwide, and treatment options remain very limited. Traditional Chinese Medicine (TCM) has been used for thousands of years to treat ischemic stroke and has been proven to have significant efficacy, but its mechanism of action is still unclear. As research related to the brain-gut-microbe axis progresses, there is increasing evidence that the gut microbiota plays an important role during AIS. The interaction between TCM and the gut microbiota has been suggested as a possible key link to the therapeutic effects of TCM. We have compiled and reviewed recent studies on the relationship between AIS, TCM, and gut microbiota, with the expectation of providing more ideas to elucidate the mechanism of action of TCM in the treatment of AIS.